Unraveling the seed endosperm proteome of the lotus (Nelumbo nucifera Gaertn.) utilizing 1DE and 2DE separation in conjunction with tandem mass spectrometry. Issue 10 (12th February 2015) - Moro, Carlo F.; Fukao, Yoichiro; Shibato, Junko; Rakwal, Randeep; Timperio, Anna Maria; Zolla, Lello; Agrawal, Ganesh Kumar; Shioda, Seiji; Kouzuma, Yoshiaki; Yonekura, Masami; Lüthje, Sabine; Deswal, Renu; et al.
<x xml:space="preserve">Abstract</x> Nelumbo nucifera (Gaertn.) or lotus, is an aquatic plant native to India, and presently consumed as food mainly in China and Japan. Lotus is also widely used in Indian and Chinese traditional medicine. Extracts from different parts of the lotus plant have been reported to show diverse biological activities—antioxidant, free radical scavenging, anti‐inflammatory, and immunomodulatory. Despite this, little work has been done in isolating and identifying proteins responsible for these activities, or yet importantly to establish a lotus proteome. The aim of our group is to develop a proteome catalog of the lotus plant, starting with its seed, the nutrient rich food source. In this present study, the seed endosperm—most abundant in proteins, and main nutrient storage tissue—was targeted for protein extraction by testing five different extraction protocols, followed by their proteomic analyses using complementary 1DE and 2DE approaches in conjunction with MS/MS. The inventory of 66 nonredundant proteins obtained by 1DE‐MS and the 30 obtained by 2DE‐MS provides the first catalog of the lotus seed endosperm, where the most abundant protein functions were in categories of metabolic activities related to carbohydrate metabolism and nutrient storage.